Poezja języka migowego jako czynnik kulturotwórczy - Rąbel, Aleksandra (Investigationes Linguisticae, 2011)
In the paper there are presented different forms of sign language poetry. They are created by the Deaf, a language and culture minority, using the natural sign language. They are also forms of games and activities and thus create a culture of deaf community. In addition, each of the described forms of poetry is refered to the Roger Caillois’s conception of a paidia-ludus axis.